Current Account and External Sustainability in the Baltics, Russia, and Other Countries of the Former Soviet Union - McGettigan, Donal (Occasional Papers; Occasional Paper ;, 2000)
Large current account imbalances have been recorded in the Baltics, Russia, and other countries of the former Soviet Union since their independence. Are these current account positions sustainable, reflecting the special circumstances of transition, or are the positions untenable over the longer term? This study attempts to address this important question by first describing recent current account developments in these transition economies. It subsequently focuses on a wide range of external sustainability indicators by drawing on the existing literature, and attempts to assess their potential usefulness in a transiton country context. The indicators examined include real exchange rates, fiscal revenues and expenditures, savings and investment developments, openness measures, growth projections, external debt composition, foreign exchange reserve cover, and various financial sector measures.